2013
DOI: 10.1097/aln.0b013e3182a95164
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Substance P-Saporin in the Dog

Abstract: Intrathecal 15-µg SP-SAP reduced dorsal, but not ventral, NK1-r (+) neurons at the spinal level of delivery with minimal side effects, whereas 150-µg SP-SAP resulted in motor neuron toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…For these reasons, future studies may need to address the issue of AAV escape from the IT space by alternate procedure of IT vector delivery such as by interventional radiology assisted lumbar puncture. Such experiments may be a valuable addition to the use of the long-standing, “gold standard” dog model that was used in the present study 30,3943 .…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, future studies may need to address the issue of AAV escape from the IT space by alternate procedure of IT vector delivery such as by interventional radiology assisted lumbar puncture. Such experiments may be a valuable addition to the use of the long-standing, “gold standard” dog model that was used in the present study 30,3943 .…”
Section: Resultsmentioning
confidence: 99%
“…, receptor or enzyme protein). The development of such data is important not only because it demonstrates confirmatory effects in another species, it has the practical benefit of being able to show the safety data studies to be constructed so as to define safety as multiples of a therapeutically effective dose in a large spinal cord (see, for example [390]).…”
Section: Current Spinal Agentsmentioning
confidence: 99%
“…Intrathecal sP-saporin has been shown to lead to a robust change in a variety of pain states in several species including the rodent [389] and dog [261]. Large animal safety studies have shown target engagement after intrathecal delivery showing local knockdown of spinal NK1-r protein and message [390]. Importantly, at high concentrations motor dysfunction was observed that reflected upon the presence of NK1-r in motor neurons in the dog.…”
Section: Toxins Coupled To Agonists For G-protein-coupled Receptorsmentioning
confidence: 98%
“…Where feasible, the drug dosing should be shown to have appropriate target engagement (e.g., behavioral endpoints, CSF concentrations, and knock-out of target marker (e.g., receptor or enzyme protein). The development of such data is important not only because it demonstrates confirmatory effects in another species, it has the practical benefit of being able to show the safety data studies to be constructed so as to define safety as multiples of a therapeutically effective dose in a large spinal cord (see, for example [390]). …”
Section: Intrathecal Drug Safety Evaluationmentioning
confidence: 99%